PENGARUH DENUKLIRISASI TERHADAP UPAYA REUNIFIKASI KOREA UTARA DAN KOREA SELATAN PERIODE 2017-2020 - Shafiya Salsabila Rusti Nuridho, (2022)
The turbulent international relations between North and South Korea originated from a grim past. The Korean War is a brief albeit arduous event, which increased the barrier between the two nations significantly. From a previously united peninsula nation, the two countries broke apart with the North under Soviet and China's iron-clad rule with an absolute socialist dictatorship rule, whereas the South favours the American ally with a capitalistic outlook. From its infancy in 1950 towards the modern era, the two sides kept their separation with a looming nuclear threat from the North haunting the South quietly in the proceeding years. However, the South has enjoyed significant economic growth with a competent defence force, whilst the Hermit Kingdom is still shrouded in mystery and stagnant economy. In recent years, threats of nuclear warfare have become more prominent, and attempts at diplomacy and conscious reconciliation have been attempted by both nations' leaders. With the passing year, tension only rises, with a significant emergency alert in early 2020 from a bigger nuclear threat towards American territories. In this study, the writer studies the history and national policies from both sides, including from political, defence, economical and social/cultural perspectives to see how the two nations have attempted to go through with a reunification amidst denuclearization attempts.